Polish Independent Press Review, no. 10 (1987) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Topical reviews of Polish samizdat publications in English prepared by RFE staff members to be used by different national broadcasting units. PIPR was published from 1986 until November 1989 as a continuation of Polish Underground Extracts (PUE). Profiles of Major Independent Polish Publications: "Krytyka - Kwartalnik Polityczny" / by Michał Kołodziej"Krytyka - Kwartalnik Polityczny" is a quarterly published in Warsaw by the NOWA and Krąg publishing houses. The "Krytyka" Political Quarterly LibraryThe editorial staff of the independent periodical "Krytyka - Kwartalnik Polityczny" also produces books for its monograph series, the Krytyka Political Quarterly Library. The Independent Press on Solidarity's New Commission / by Anna PomianThe independent press's initial reactions to the creation of Solidarity's National Executive Commission indicate that a new phase of coordinated overt action is envisaged. The Interim Coordinating Commission: 22 April 1982 to 25 October 1987 / by Michał KołodziejThis is the first part of an article on Solidarity's Interim Coordinating Commission, which was dissolved in October. This article looks at the formation, objectives, activities, membership, and organization of the commission. The Significance and Role of the Interim Coordinating Commission / by Michał KołodziejThis is the second part of an article on the Interim Coordinating Commission. The Commission was repeatedly criticized in the underground press and was accused of being incapable of finding ways to restore Solidarity's legal status. It enjoyed considerable authority among the public, however, it left behind many achievements in the creation of an independent society.